Developing A Basic Grammar Teaching Skills Guide Using Aspiring Suite (Ispring Suite) at Nurul Yaqin Institute, Batu Ateh Datar - Wahyuni, Sisri; Aisyah, Devy (Journal International of Lingua and Technology, 2025)
The purpose of this study was to provide the need, feasibility and practicality of the Ispring Suite-assisted Teaching Skills Guidebook to Improve Professional Teachers of Nurul Yaqin Islamic Boarding School in Batipuh Ateh Tanah Datar. The research method to be applied in this study is the 4D research and development (R&D) model, which involves four stages, namely define, design, develop, and disseminate. This research focuses on the first three stages, namely define, design, and develop. The participants in this study were nine Arabic language subject teachers using the yellow book at Pondok Pesantren Nurul Yaqin Nurul Yaqin Batipuh Ateh Tanah Datar. Data collection was carried out through validity sheets and practicality sheets as research instruments. The result of the research is that the basic guide material for teaching Arabic using iSpring Suite is Very Effective to use.